2021
DOI: 10.3389/fcimb.2021.660415
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factors Interplay Orchestrates the Immune-Metabolic Response of Leishmania Infected Macrophages

Abstract: Leishmaniasis is a group of heterogenous diseases considered as an important public health problem in several countries. This neglected disease is caused by over 20 parasite species of the protozoa belonging to the Leishmania genus and is spread by the bite of a female phlebotomine sandfly. Depending on the parasite specie and the immune status of the patient, leishmaniasis can present a wide spectrum of clinical manifestations. As an obligate intracellular parasite, Leishmania colonize phagocytic cells, mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 176 publications
0
13
0
Order By: Relevance
“…Indeed, we identified 41 L-CK1.2 host substrates involved in apoptosis, such as BCL2L13, which regulates the role of mitochondria-mediated cell death pathway and can be pro- or anti-apoptotic ( Meng et al, 2021 ), or FOXO3, which is a transcription factor inducing transcription of genes involved in apoptosis. There are other examples with host pathways such as “actin cytoskeleton organisation’ or RNA metabolic process” that are both targeted by L-CK1.2 and modified during Leishmania infection ( Fernandes et al, 2016 ; de Menezes et al, 2017 ; Smirlis et al, 2020 ; Bichiou et al, 2021 ). Extensive work remains to be done to ascertain the link between L-CK1.2 and host pathways modified during Leishmania infection.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we identified 41 L-CK1.2 host substrates involved in apoptosis, such as BCL2L13, which regulates the role of mitochondria-mediated cell death pathway and can be pro- or anti-apoptotic ( Meng et al, 2021 ), or FOXO3, which is a transcription factor inducing transcription of genes involved in apoptosis. There are other examples with host pathways such as “actin cytoskeleton organisation’ or RNA metabolic process” that are both targeted by L-CK1.2 and modified during Leishmania infection ( Fernandes et al, 2016 ; de Menezes et al, 2017 ; Smirlis et al, 2020 ; Bichiou et al, 2021 ). Extensive work remains to be done to ascertain the link between L-CK1.2 and host pathways modified during Leishmania infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, its impact on cellular metabolism seem to depend on the cell type and to our knowledge no studies have investigated the role of NLRX1 on macrophage colony stimulating factor (M-CSF) primed BMDM metabolism ( 87 ). Leishmania and other intracellular pathogens are known to manipulate host metabolism and Leishmania infection seems to favor a switch to aerobic glycolysis ( 88 , 89 ). Here we showed that infection with Lgy parasites induced glycolysis in infected BMDMs while maintaining a high OXPHOS activity.…”
Section: Discussionmentioning
confidence: 99%
“…major suppresses macrophages production of IL‐12 by inducing the expression of monarch‐1 molecule found on macrophages which negatively regulates NF‐kB 38 . During infection of macrophages by Leishmania , the parasite can cause the blockade of active p65/p50 as well as inducing the p50/p50 repressor causing the effective blockade of IFN‐ɣ‐mediated NO production by macrophages 39‐41 …”
Section: Paradoxical Immunity—leishmania Parasite Interactionsmentioning
confidence: 99%
“…38 During infection of macrophages by Leishmania, the parasite can cause the blockade of active p65/p50 as well as inducing the p50/p50 repressor causing the effective blockade of IFN-ɣ-mediated NO production by macrophages. [39][40][41] In a similar scenario, Leishmania parasite surface molecules are potent tools used by the parasite to counter macrophagic response. For instance, several studies have reported how Leishmania subvert macrophages microbicidal arsenal by using lipophosphoglycan (LPG), the most abundant virulent surface molecules produced by Leishmania to target phagosome membrane and maturation.…”
Section: Macrophage-leishmania Interactionmentioning
confidence: 99%